All-cause and cause-specific mortality among individuals imprisoned for driving under the influence of alcohol and drugs in Norway (2000–2016): a retrospective cohort study - Ragnhild Elén Gjulem Jamt; Stig Tore Bogstrand; Anne Bukten; Marianne Riksheim Stavseth; Torill Tverborgvik (BMJ Open)
Aims To describe all-cause and cause-specific mortality and to investigate factors associated with mortality among individuals imprisoned for driving under the influence (DUI) of alcohol and psychoactive drugs in the Norwegian prison population.Design Retrospective cohort study. The Norwegian prison registry was linked to the Norwegian Cause of Death Registry (2000–2016).Setting Norway.Participants/cases The cohort consisted of 96 856 individuals imprisoned in Norway over a 17-year period obtained from the Norwegian prison registry.Primary and secondary outcome measures Adjusted ORs (aOR) with 95% CI were calculated for death due to any, natural and unnatural causes of death. Analyses were stratified according to DUI convictions: no DUI convictions, only DUI convictions (DUI only), DUI and at least one other drug and alcohol conviction (DUI drug), and DUI and at least one conviction other than drug and alcohol conviction (DUI other).Results In total, 29.3% individuals had one or more imprisonments for DUI. The risk of all-cause mortality was elevated for those convicted for DUI, but only in combination with other types of crimes (DUI drug: aOR=1.5, 95% CI 1.4 to 1.6, DUI other: aOR=1.2, 95% CI 1.1 to 1.4). The risk of death from natural causes was significantly elevated for DUI drug (aOR: 1.8, 95% CI 1.6 to 2.0) and for DUI other (aOR=1.3, 95% CI 1.1 to 1.6). The risk of death from unnatural causes was lower for DUI only (aOR=0.8, 95% CI 0.7 to 0.9) and elevated for DUI drug (aOR=1.5, 95% CI 1.3 to 1.6).Conclusions The risk of all-cause mortality was significantly elevated for those convicted of DUI, but only in combination with other types of crimes.